A Fractured Self: AN's Journey Through Borderline Personality Disorder and Therapeutic Resilience (Kerala Journal of Psychiatry, 2026)
AN, a 28-year-old female artist, presented with a complex constellation of symptoms indicative of borderline personality disorder (BPD), including intense emotional dysregulation, unstable interpersonal relationships, a distorted self-image, and chronic feelings of emptiness. Her history was a harrowing narrative of childhood trauma, weaving a tapestry of emotional wounds that profoundly impacted her adult life. This case report details her journey through a multifaceted therapeutic approach encompassing Cognitive Behavioral Therapy (CBT), Dialectical Behavior Therapy (DBT), Supportive Therapy, Behavioral Therapy, and intensive Arts-Based Therapy (ABT). It explores the challenges and triumphs encountered during her treatment, highlighting the importance of a well-tailored, integrative approach in addressing the unique complexities of BPD. It also examines the nuanced dynamics of the therapist-client relationship, emphasizing the crucial role of consistent support and the gradual development of self-efficacy in facilitating AN's path toward healing and stability.
Keywords: Borderline Personality Disorder; Cognitive Behaviour Therapy; Dialectical Behaviour Therapy; Art Therapy